Islamic Civilization: Sources Of Moderation And Manifestations Of Extremism - Benkheira, Nadjib (جامعة الوادي - University of Eloued, 2019)
The intellectual and economic stagnation that Muslim countries seem to suffer currently has resulted in self-doubt and suspicious scrutiny, by Muslims, of their cultural heritage and the foundations of their civilization. However, a strong sense of affinity to their culture has led many to believe that theirs is the morally stronger culture even though it is the weakest in material terms. The real conundrum here is this: why has the Muslim Civilization, with its strong emphasis on moderation and enlightenment and a glowing record in applying these principles, now become the source of some appalling manifestations of intellectual extremism and behavioral perversion. This paper will attempt to answer this question while exploring three main issues: I. Sources of Moderation in Islamic Civilization.
مقال
Keywords: Peaceful -coexistence-- Religious - moderation - Intellectual -temperance